2012
DOI: 10.4103/1735-3327.95226
|View full text |Cite
|
Sign up to set email alerts
|

Recharge pattern of contemporary glass ionomer restoratives

Abstract: Background:As glass ionomers have the ability to reload fluoride from outside sources, the aim was to compare the recharge pattern of six glass ionomer cements after exposure to fluoride.Materials and Methods:Fuji VII, Fuji IX, Riva Pink, Riva Bleach, Ketac Fil and Fuji IX Extra were investigated. The fluoride-containing materials used were tooth paste and mouth wash (Colgate). Specimens of each material (n=15) were immersed separately in deionized water for 59 days. Then the samples of each material were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
16
0
3
Order By: Relevance
“…It may not be necessary, nor even desirable, to completely cover the tooth surface in order to gain sufficient protection. A major advantage of using a glass ionomer cement is that it is possible to recharge the reservoir in the protection material for ongoing release of fluoride . Recharging of fluoride using microcapsules embedded into orthodontic cements has also been demonstrated .…”
Section: Surface Protection Of Teeth Undergoing Orthodontic Treatmentmentioning
confidence: 99%
“…It may not be necessary, nor even desirable, to completely cover the tooth surface in order to gain sufficient protection. A major advantage of using a glass ionomer cement is that it is possible to recharge the reservoir in the protection material for ongoing release of fluoride . Recharging of fluoride using microcapsules embedded into orthodontic cements has also been demonstrated .…”
Section: Surface Protection Of Teeth Undergoing Orthodontic Treatmentmentioning
confidence: 99%
“…The dentifrice recommended in this study may have increased fluoride levels and thereby prevented secondary caries. 32,33 Tooth sensitivity before restorative rehabilitation may be reduced with the help of self-etch adhesive systems. Perdigão and others 28 reported that postoperative sensitivity to air improved significantly with different self-etch adhesive systems.…”
Section: Discussionmentioning
confidence: 99%
“…Os dois CIVs testados apresentaram um padrão de liberação semelhante ao descrito na literatura, caracterizado pelo elevado teor de flúor liberado nas primeiras horas e acentuado declínio nos dias subsequentes 4,10,11 .…”
Section: Discussionunclassified